Control de costos en edificio de tres niveles - Cordero-Campos, Diego Andrés (Instituto Tecnológico de Costa Rica, 2017)
The purpose of this study is to improve and strengthen the cost control system of Grupo Condeco Vac S.A. The development starts with an analysis of the actual situation of the company this was generated with a compilation of information focus on cost control and with an exploration of the system used by the company. The results give a perspective of the strengths, disadvantages and the points to improve. A literature investigation about monitoring and control process was made and combined with the results obtain in the analysis of the actual situation of the system a new model of three tools was designed and created. The new tools were made with Microsoft Excel. The development of this document was possible by using interviews, checking files, making literature investigations and using the tools in a construction project. This study expose a report generated on a establish date. The report describes all the results obtained by using the new tools.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2017.
Keywords: Sistemas; Control; Costos; Diseño; Construcción